Evaluation and characterization of sorghum biomass as feedstock for sugar production. - Theerarattananoon, Karnnalin; Wu, Xiaorong; Staggenborg, Scott A.; Propheter, R.; Madl, Ronald L.; Wang, Donghai (My University, 2010)
Conversion of cellulosic biomass, such as agricultural residues, to biofuels offers significant economic, environmental, and strategic benefits. Sorghum is an important energy crops in the U.S. It is a renewable resource and is currently grown on about 10 million acres in the U.S. However, at present, there is a lack of scientific information and knowledge about the use of sorghum biomass for biofuel production. The objective of this research was to evaluate and characterize sorghum biomass as a feedstock for sugar production. Five types of sorghum biomass (brown midrib sorghum, forage sorghum, grain sorghum, photoperiod-sensitive sorghum, and sweet sorghum) were characterized and evaluated for sugar production. Pretreatment with dilute acid was used to increase yield of fermentable sugars. Effects of sulfuric acid concentration, treatment temperature, and residence time on yield of fermentable sugars were studied. Accellerase 1000 was used to hydrolyze cellulose into glucose at 50°C and pH 4.8 for 96 h. A high percentage of enzymatic conversion of cellulose (ECC) was observed for sorghum biomass that was pretreated under severe pretreatment temperature (85% to 98% ECC for biomass pretreated at 165°C for 10 min; 65% to 82% ECC for biomass pretreated at 140°C for 30 min). However, mass recovery and cellulose recovery of the solid fraction after pretreatment decreased under severe pretreatment conditions (70% to 85% cellulose recovery for sorghum biomass pretreated at 140°C for 30 min; 31% to 58% cellulose recovery for sorghum biomass pretreated at 165°C for 10 min).
Keywords: Cellulose conversion; Enzymatic hydrolysis; Pretreatment; Sorghum biomass